The Essence of Islamic Education Management and Development Perspective of Islamic Education Philosophy - Harahap, Aidul Azhari (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
The management and development of Islamic education is a necessity that is carried out to achieve the actual goals of Islamic education which of course cannot be separated from the management and use of human resources properly and in accordance with their portions. Human resources, such as teachers as teachers and educators for students in Islamic educational institutions or environments, are decisive in achieving learning processes that demand intellectual success and Islamic values for their students. However, this is the duty and obligation of a manager in sorting out and carrying out proper empowerment for his educators. In addition, the process of deliberation is one of the methods that can be implemented for matters relating to obstacles or problems encountered in the educational process carried out in Islamic educational institutions themselves.